PENDEKATAN DAN STRATEGI PENDIDIKAN NILAI DI ERA GLOBALISASI UNTUK PEMBENTUKAN KARAKTER PESERTA DIDIK - Rifki, Muchamad; Wahyuni, Neneng Sri; Nasrullah, Fathonah; Hidayatuloh, Abdul Aziz; Hasan, Muhammad (Penerbit Widina, Widina Media Utama, 2025)
This study examines the urgency of value education in the era of globalization, as well as the approaches and strategies that can be applied in learning processes to shape students’ character. Globalization brings positive impacts such as easier access to information and improved skills, but it also presents challenges including moral degradation, weakened cultural identity, and increasing individualism. Therefore, value education must be positioned as an integral part of the learning process. This research employs a library research method by analyzing literature related to value education, learning approaches, and character-building strategies. The findings indicate that value education can be internalized through approaches such as role modeling, habituation, value dialogue, value clarification, and curriculum integration. This study identifies that the combination of role modeling and habituation represents the most effective strategy within the context of formal education in Indonesia. In addition, active learning, collaborative learning, and project-based learning provide opportunities for students to understand and practice values through real-life experiences. This research offers a conceptual contribution to the development of value-education practices based on curriculum integration and active learning in schools.ABSTRAKPenelitian ini membahas urgensi pendidikan nilai di era globalisasi serta pendekatan dan strategi yang dapat diterapkan dalam proses pembelajaran untuk membentuk karakter peserta didik. Globalisasi membawa dampak positif berupa kemudahan akses informasi dan peningkatan keterampilan, namun juga menimbulkan tantangan seperti degradasi moral, melemahnya identitas budaya, dan meningkatnya individualisme. Oleh karena itu, pendidikan nilai perlu ditempatkan sebagai bagian integral dari pembelajaran. Penelitian ini menggunakan metode studi kepustakaan dengan menganalisis literatur terkait pendidikan nilai, pendekatan pembelajaran, dan strategi implementasi karakter. Hasil kajian menunjukkan bahwa pendidikan nilai dapat di internalisasi melalui pendekatan keteladanan, pembiasaan, dialog nilai, klarifikasi nilai, serta integrasi nilai dalam kurikulum. Kajian ini menemukan bahwa kombinasi pendekatan keteladanan dan pembiasaan merupakan strategi yang paling efektif dalam konteks pendidikan formal di Indonesia. Selain itu, strategi pembelajaran aktif, kolaboratif, dan berbasis proyek memberikan ruang bagi peserta didik untuk memahami dan mempraktikkan nilai dalam pengalaman nyata. Penelitian ini memberikan kontribusi konseptual dalam pengembangan praktik pendidikan nilai berbasis integrasi kurikulum dan pembelajaran aktif di sekolah.